Giving A Variety of Fermented Tauge Flour Levels to The Percentage of Carbon and Giblet Broiler Chicken Age 5 Weeks - I Komang Agus Andika Sudarsana; Ni Ketut Sri Rukmini; Luh Suariani (Warmadewa University Press, 2019)
The commodity of poultry that has the greatest potential to be developed is broiler chicken because its growth is fast so the maintenance period is relatively short. The purpose of this study was to determine the effect of fermented bean sprouts flour on the percentage of carcasses and giblets as well as what level of fermented bean sprout flour administration in rations that affected the percentage of carcasses and giblets of broiler chicken CP 707. The design used in this study was a Completely Randomized Design (CRD) with 4 treatments and 3 replications. At each test using 4 CP 707 broiler chickens aged 2 weeks with homogeneous body weight. The treatments are P0 (control ration without fermented bean sprout flour), P1 (ration containing fermented bean sprout flour 3%), P2 (ration containing 6% fermented bean sprout flour), and P3 (ration containing 9% fermented bean sprout flour). The parameters observed were the percentage of carcasses and giblets (heart, liver, gizzard). The provision of various levels of fermented bean sprouts waste flour had no significant effect (P>0.05) on the percentage of carcasses and giblets of broiler chickens aged 5 weeks.